2019
DOI: 10.1007/s10048-018-0561-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ribosomal protein PTCD3 mutations cause oxidative phosphorylation defects with Leigh syndrome

Abstract: Pentatricopeptide repeat domain proteins are a large family of RNA-binding proteins involved in mitochondrial RNA editing, stability, and translation. Mitochondrial translation machinery defects are an expanding group of genetic diseases in humans. We describe a patient who presented with low birth weight, mental retardation, and optic atrophy. Brain MRI showed abnormal bilateral signals at the basal ganglia and brainstem, and the patient was diagnosed as Leigh syndrome. Exome sequencing revealed two potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…Exome analysis was performed as previously described [12]. Whole-exome sequencing was performed using the HiSeq2500 (Illumina, San Diego, CA, USA) platform, and for the alignment of the sequencing reads the NCBI human genome reference (GRCh37/hg19) was used.…”
Section: Genetic Analysis and Sanger Sequence Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Exome analysis was performed as previously described [12]. Whole-exome sequencing was performed using the HiSeq2500 (Illumina, San Diego, CA, USA) platform, and for the alignment of the sequencing reads the NCBI human genome reference (GRCh37/hg19) was used.…”
Section: Genetic Analysis and Sanger Sequence Validationmentioning
confidence: 99%
“…Spectrophotometric enzyme activity assays using MT from fibroblasts and lentiviral-mediated transduced samples were performed as previously followed [12].…”
Section: Oxphos Enzyme Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the RNA components of the mitochondrial translation machinery are encoded in mtDNA, the protein components of the ribosome and accessory proteins such as aminoacyl tRNA synthetases being nuclearly encoded. Mutations in nuclear genes encoding protein components of the ribosome affect the accuracy of translation and are associated with a diverse range of pathologies including ovarian insufficiency [ 260 ], encephalopathy [ 261 ], Leigh syndrome [ 262 ] and stress related behavioral alterations in mice [ 263 ]. A similar diversity of presentation is seen in mutations affecting mitochondrial aminoacyl tRNA synthetases and the reasons for this diversity from an apparently similar mechanism are discussed by González-Serrano [ 264 ].…”
Section: Genetics Of Mitochondrial Dnamentioning
confidence: 99%
“…A study of PTCD3 knockdown showed protein synthesis was seriously disturbed to result in OXPHOS de ciency, although no effect on RNA metabolism 41 . PTCD3 mutations led to impaired translation of mtDNA-encoded proteins, resulting in combined defects of Complex I and IV, and decreased ATP production 42 . Although MRPL4 had not been reported in the mitochondrial diseases, this molecule had attracted increasing attention from researchers because it had been reported to be downstream of hypoxia-inducible factor-1α (HIF-1α) 43 .…”
Section: Melasmentioning
confidence: 99%